2008
DOI: 10.1007/s10460-008-9138-9
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic determinants of keeping goats and sheep by rural people in southern Benin

Abstract: An understanding of factors influencing the decision of rural people to keep sheep and/or goats is crucial when formulating technologies and policies that support village-based small ruminant production. The knowledge of such factors will also improve assessment of impact intervention strategies on the livelihoods of rural people. Structured questionnaires administered in 228 households were used to study the ownership patterns of small ruminants in southern Benin. The ownership of goats was higher (91%) than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 39 publications
(46 reference statements)
7
29
0
3
Order By: Relevance
“…Their results showed that a greater percentage of the smallholder goat enterprise had a mean age of 52.7 years with a bias towards the female gender who represented 70 % of the goat farmers in the state. This result is also a confirmation of Dossa et al (2008) in southern Benin Republic where goat ownership is much of women business. It is interesting to note that 80.6 % of the farmers were married with 68.7 % having formal education.…”
Section: Socio-economic Characteristics Of Smallholder Goat Enterprisesupporting
confidence: 69%
“…Their results showed that a greater percentage of the smallholder goat enterprise had a mean age of 52.7 years with a bias towards the female gender who represented 70 % of the goat farmers in the state. This result is also a confirmation of Dossa et al (2008) in southern Benin Republic where goat ownership is much of women business. It is interesting to note that 80.6 % of the farmers were married with 68.7 % having formal education.…”
Section: Socio-economic Characteristics Of Smallholder Goat Enterprisesupporting
confidence: 69%
“…This concurs with literature that the smallholder farmers in South Africa are mostly above the age of 40 (Marandure et al, 2016;Motiang & Webb, 2016). It could be due to the effects of migration of young rural residents to urban areas in search of better working and living conditions (Dossa et al, 2008). In addition, the rural youth are generally not interested in agriculture as a career.…”
Section: Discussionmentioning
confidence: 99%
“…This in particular could be proven by the lower average age of the non-camel-owning household heads who also highlighted that the initial cost of acquiring camels was prohibitive. Studies by Dossa et al (2008) and Kabubo-Mariara (2008) showed a connection between age and wealth particularly of livestock in pastoral production systems.…”
Section: Determinants Of Camel Productionmentioning
confidence: 99%